Immunotherapy in Gastric Carcinoma: Current Status and Future Perspectives - Kankeu Fonkoua, Lionel; S Yee, Nelson (Clinical Cancer Drugs, 2015)
Background: Gastric carcinoma (GC) is a globally prevalent malignant disease and it is associated with a high mortality rate. Recent advances have been made in development of immunotherapies that aim at modulating the patients’ immune system and the tumor-associated microenvironment. Methods: The field of cancer immunology that is pertinent to GC was provided. The basis for immunotherapeutic approaches to advanced GC was reviewed. Results of the clinical studies obtained from the literature in PubMed as well as the ongoing clinical trials as listed in www.ClinicalTrials.gov were described and discussed. Results: One major approach of immunotherapy in GC employs therapeutic antibodies that target mitogenic signaling pathways, angiogenesis, and immune checkpoint molecules. Clinical studies have demonstrated efficacy using trastuzumab and ramucirumab that target human epidermal growth factor receptor 2 and vascular endothelial growth factor receptor 2, respectively. Other approaches involve adoptive transfer of cellular mediators of immune response as well as tumor cell-based vaccines. Conclusion: The success of antibody-based therapy has been limited by genetic heterogeneity of GC and plasticity of the molecular targets. Immunotherapeutic approach as monotherapy in GC has not produced the desirable clinical outcomes. Novel strategies that target multiple driver mutations of gastric tumorigenesis and combination of immuno-, chemo-, and radiation therapy will hopefully create new opportunity to improve the treatment outcomes. An integrative approach using molecular tumor profiling and targeted immunotherapeutics is expected to make a positive impact towards the goal of precision therapy in this highly lethal malignancy.
Keywords: ramucirumab